Using SETS Approach on Cognitive Learning Achievement and Naturalist Intelligence of Elementary School Fourth Grade Students (Journal of Primary Education, 2017)
The purpose of this research was to compare the effectiveness of guided inquiry learning with SETS approach and lecturing on cognitive learning achievement and naturalist intelligence of fourth grade elementary school students. This research used quasy experimental design, pretest-postest control group type design with guided inquiry learning SETS approach as independent variable. The dependent variable is the cognitive learning achievement and naturalist intelligence. The results of this research found that the students' cognitive learning achievement increases after being teached by using guided inquiry learning SETS approach that compare to discussion and lecturing. There is significant difference of learning achievements that apply the guided inquiry learning with SETS approach compared to the discussion and lecturing. Guided inquiry learning is more effective in improving cognitive learning achievement of fourth grade students. There is a high naturalist intelligence on the application of guided inquiry learning with SETS approach on science subject. It is suggested to teachers to apply guided inquiry learning with SETS approach in order to improve cognitive learning and naturalist intelligence. The use of guided inquiry learning with SETS approach should be priopritized in learning.